2008
DOI: 10.22621/cfn.v122i3.605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Cover on Fruit Set in the Woodland Herb, <em>Maianthemum canadense</em> (Liliaceae)

Abstract: . 2008. Effects of forest cover on fruit set in the woodland herb, Maianthemum canadense (Liliaceae). Canadian Field-Naturalist 122(3): 234-238.Animal pollination has been recognized as an essential ecosystem function that is potentially under various environmental stresses. We investigated the landscape effects of forest cover at multiple spatial scales on the sexual reproductive success of a common woodland herb in North America, Maianthemum canadense. This species is a self-incompatible species and pollinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…There were instances of isolation benefiting plant species by increasing fecundity [Cascante‐Marin et al . ; although the increase in flowers may not translate to an increase in seeds (Taki, Kevan & Yamaura )], decreasing herbivory/predation (Farwig et al . ) and by increasing colonization, mainly of wind dispersed species [Graae ; although these may also be negatively affected by isolation (Soons et al .…”
Section: Discussionmentioning
confidence: 99%
“…There were instances of isolation benefiting plant species by increasing fecundity [Cascante‐Marin et al . ; although the increase in flowers may not translate to an increase in seeds (Taki, Kevan & Yamaura )], decreasing herbivory/predation (Farwig et al . ) and by increasing colonization, mainly of wind dispersed species [Graae ; although these may also be negatively affected by isolation (Soons et al .…”
Section: Discussionmentioning
confidence: 99%
“…This light is associated with higher understory plant species richness and abundance, especially of shade-intolerant, early-successional species (Fye 1972;Bouget and Duelli 2004;Shields and Webster 2007;Falk et al 2010). As herbaceous cover increases, so does the amount of floral resources (Romey et al 2007;Quintero et al 2010) and, despite evidence that forest loss in fragmented landscapes can be deleterious to plantpollinator interactions (Didham et al 1996;Kearns et al 1998;Steffan-Dewenter et al 2002;Taki et al , 2008, many studies in continuously forested ecosystems have shown that disturbance increases abundance and richness of insect pollinators (e.g., Bouget and Duelli 2004;Nol et al 2006;Campbell et al 2007;Romey et al 2007;Deans et al 2007). …”
mentioning
confidence: 99%
“…The common woodland herb Maianthemum canadense is self‐incompatible and requires pollination by insects (particularly hoverflies and bees) (Taki et al, 2008). This plant has been found to have a decreased sexual reproductive output due to the loss of insect pollinators where pesticides have been used to treat forest pests (Kevan & Plowright, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Hog peanut does, however, have plasticity within its mating system, which allows the plant to adjust its reproductive strategy based on environmental conditions (Trapp & Hendrix, 1988). To have the ability to outcross between populations, this requires the management of plant populations of adequate size and within an appropriate distance for access by relevant pollinators (Taki et al, 2008). This is a key feature for avoiding inbreeding depression in plant populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation